Peran SMA Islam Al Azhar 21 Sukabumi Berbasis Cambridge sebagai Upaya Peningkatan Kemampuan Berbahasa Inggris - Muhamad Naufal Firdaus; Siti Qomariyah; Dudi Muharam; Hoerul Anwar; Rhama Dian Putra (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the role of Cambridge-based Islamic High Schools in improving English language skills. The background of this study is because education in the 21st century is characterized by very rapid technological developments and globalization. This study was conducted at Al Azhar 21 Islamic High School, Sukabumi, focusing on 4 discussions, namely: (1) The concept of Cambridge-based Islamic High Schools (2) Strategies for Cambridge-based Islamic High Schools in efforts to improve English language skills (3) The role of Cambridge-based Islamic High Schools in improving English language skills (4) Obstacles and solutions for Cambridge-based Islamic High Schools in efforts to improve English language skills. This study uses descriptive qualitative methods through observation, interviews, and documentation. The results of the study indicate that Cambridge-based Islamic High Schools have a significant and structured role because English is not only studied, but also used as a primary tool for learning and critical thinking at the academic level. The main obstacle comes from the readiness and competence of human resources (Teachers and Students) so that the solution is to hold an acceleration program for students who have never followed or studied using the Cambridge curriculum and also hold official training and certification from Cambridge in stages.